Der Tonwille, Volume I : Pamphlets in Witness of the Immutable Laws of Music Volume I: Issues 1-5 (1921-1923). - Schenker, Heinrich (Oxford University Press, 2002)
This is the first volume of a two-volume translation of Heinrich Schenker's 'Der Tonwille' (1921-24). This book includes Schenker's original, major essays on Beethoven's Fifth Symphony and piano sonatas by Haydn, Mozart, and Beethoven, shorter analyses of Bach preludes and more.